The role of social media orientation to improve relationship quality and innovation performance in SME’s / Adelia Ika Damayanti, Ardian Adhiatma and Olivia Fachrunnisa - Damayanti, Adelia Ika; Adhiatma, Ardian; Fachrunnisa, Olivia (2020)
This study aims to determine how the role of social media orientation towards the quality of relationships and innovation performance through sharing or gathering knowledge between organizations in SMEs. The rise of the use of social media is an attraction for SMEs to look for in maintaining good relations with stakeholders. With easy access and extensive networks, social media will be able to have a positive and beneficial impact on SMEs. Therefore, social media can play a role in inter organizational knowledge sharing about SMEs to produce good relationship quality with customers and other SMEs that are industrially based on their value congruence which will improve SMEs innovation performance. Data obtained from 109 SMEs owners in Indonesia with the criteria of using digital technology (social media) as a business tool and has been operating for 1 year. Data collection was carried out using a questionnaire which was further analysed using Partial Least Square (PLS). The results showed that there was a positive and significant influence on social media orientation on inter organizational knowledge sharing while inter organizational knowledge sharing had a positive and significant effect on relationship quality and innovation performance, and value congruence could also moderate the relationship between inter organizational knowledge sharing and relationship quality.